Microenvironment and phylogenetic diversity of Prochloron inhabiting the surface of crustose didemnid ascidians. (11th August 2015) - Nielsen, Daniel A.; Pernice, Mathieu; Schliep, Martin; Sablok, Gaurav; Jeffries, Thomas C.; Kühl, Michael; Wangpraseurt, Daniel; Ralph, Peter J.; Larkum, Anthony W. D.
Summary The cyanobacterium Prochloron didemni is primarily found in symbiotic relationships with various marine hosts such as ascidians and sponges. Prochloron remains to be successfully cultivated outside of its host, which reflects a lack of knowledge of its unique ecophysiological requirements. We investigated the microenvironment and diversity of Prochloron inhabiting the upper, exposed surface of didemnid ascidians, providing the first insights into this microhabitat. The pH and O2 concentration in this Prochloron biofilm changes dynamically with irradiance, where photosynthetic activity measurements showed low light adaptation (Ek ∼80 ± 7 μmol photons m−2 s−1) but high light tolerance. Surface Prochloron cells exhibited a different fine structure to Prochloron cells from cloacal cavities in other ascidians, the principle difference being a central area of many vacuoles dissected by single thylakoids in the surface Prochloron. Cyanobacterial 16S rDNA pyro‐sequencing of the biofilm community on four ascidians resulted in 433 operational taxonomic units (OTUs) where on average −85% (65–99%) of all sequence reads, represented by 136 OTUs, were identified as Prochloron via blast search. All of the major Prochloron‐OTUs clustered into independent, highly supported phylotypes separate from sequences reported for internal Prochloron, suggesting a hitherto unexplored genetic variability among Prochloron colonizing the outer surface of didemnids.